Energy Services Market Development : Scaling Up Energy Efficiency in Buildings in the Western Balkans - Limaye, Dilip; Singh, Jas; Hofer, Kathrin (World Bank Group, Washington, DC, 2014)
The development of private sector energy service providers (ESPs), including energy service companies (ESCOs), that specialize in energy efficiency (EE) project development and implementation can help overcome some of the important barriers to scaling up implementation of energy efficiency (EE) projects, particularly in the public sector. ESPs can offer a range of services spanning the energy services value chain and provide the technical skills and resources needed to identify and implement EE opportunities, perform services using performance based contracts (thereby reducing the risks to the energy users), facilitate access to financing from commercial lenders, and enable the energy users to pay for the services from the cost savings achieved. This guidance note provides examples of actions taken by governments in many countries (such as Armenia, Bulgaria, Croatia, Czech Republic, Germany, Hungary, and India) to foster the energy services market and help establish and grow ESPs in their countries. Experience from these countries shows that governments need to adopt a three-pronged approach, involving policy and regulatory initiatives, technical assistance (TA), and financing strategies, to build ESP and public agency capacity, implement ESP projects in the public sector, and provide the platform for moving to more complex implementation and financing models in the future. TA or financing alone does not offer an effective strategy to overcome the multidimensional challenges of ESP market development; efforts in all three areas are needed. Key conclusions of this guidance note are that: (i) there is no specific formula that can be prescribed to instruct governments on how to develop energy services markets; and (ii) fostering the ESP market requires governments to undertake a concerted set of legislative, regulatory, policy, financing, and awareness and information initiatives.